Circulating Cytokines and Alarmins Associated with Placental Inflammation in High‐Risk Pregnancies. (28th May 2014) - Girard, Sylvie; Heazell, Alexander E. P.; Derricott, Hayley; Allan, Stuart M.; Sibley, Colin P.; Abrahams, Vikki M.; Jones, Rebecca L.
<x xml:space="preserve">Abstract</x> Problem Inflammation during pregnancy has devastating consequences for the placenta and fetus. These events are incompletely understood, thereby hampering screening and treatment. Method of study The inflammatory profile of villous tissue was studied in pregnancies at high‐risk of placental dysfunction and compared to uncomplicated pregnancies. The systemic inflammatory profile was assessed in matched maternal serum samples in cases of reduced fetal movements (RFM). Results Placentas from RFM pregnancies had a unique inflammatory profile characterized by increased interleukin (IL)‐1 receptor antagonist and decreased IL‐10 expression, concomitant with increased numbers of placental macrophages. This aberrant cytokine profile was evident in maternal serum in RFM, as were increased levels of alarmins (uric acid, HMGB1, cell‐free fetal DNA). Conclusion This distinct inflammatory profile at the maternal‐fetal interface, mirrored in maternal serum, could represent biomarkers of placental inflammation and could offer novel therapeutic options to protect the placenta and fetus from an adverse maternal environment.